Analysis of Drug Needs Planning at the Pharmacy Installation of Dirgahayu Hospital, Samarinda - Febby Floresita Gamas (Unit Penelitian dan Pengabdian Kepada Masyarakat (UPPM) STIKES Dirgahayu Samarinda, 2022)
Drug management in hospitals is how to manage these stages and activities so that they can run well and complement each other so that the goal of effective and efficient drug management is achieved so that the drugs needed by doctors are always available when needed in sufficient quantities and guaranteed quality. to support quality services. The purpose of the study was to analyze the planning of drug needs in the hospital pharmacy installation. Qualitative descriptive analysis using data from interviews and observations. In this study, interviews were conducted with informants, namely, pharmacists and pharmacists at Dirgahayu Hospital Samarinda to determine the process of planning drug needs at the Pharmacy Installation of Dirgahayu Hospital. The results showed that the suitability of the drug item with the formulary was 85%, which means that it is in accordance with the standard, the deviation of planning is 17% which means that it is in accordance with the established standard. The results of interviews with pharmacy staff showed that the Pharmacy Installation at the Dirgahayu Hospital in Samarinda rarely experienced drug vacancies, so overall it showed that the drug planning at the Dirgahayu Hospital had been implemented well. Given the importance of drugs for hospitals, their management must be carried out effectively and efficiently so that they can provide the maximum benefit for patients and hospitals.